2003
DOI: 10.1177/01708406030247007
|View full text |Cite
|
Sign up to set email alerts
|

Repairing Managerial Knowledge-Ability Over Distance

Abstract: Despite a growing acknowledgement in the literature of the `socially embedded' character of organizational knowledge, in this article we argue that conceptualizations of knowledge management have remained aloof from the agency that they seek to inform, particularly in relation to managing within physically dispersed organizations. We seek, therefore, to explore the essential link between knowledge and action (`knowledge-ability') through an empirical investigation of the organizational conditions and manageria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 48 publications
1
39
0
1
Order By: Relevance
“…Goodall and Roberts (2003b) described the damage of geographical distance to the MNC's managerial ability. Birkinshaw (2001) found that geographically isolated groups are often shut out of the loop of knowledge sharing.…”
Section: Physical Distancementioning
confidence: 99%
See 1 more Smart Citation
“…Goodall and Roberts (2003b) described the damage of geographical distance to the MNC's managerial ability. Birkinshaw (2001) found that geographically isolated groups are often shut out of the loop of knowledge sharing.…”
Section: Physical Distancementioning
confidence: 99%
“…Past studies in international knowledge management focus on the significance of knowledge and its transfer process rather than the micro-level complexities and operational difficulties of building organisational knowledge across-borders. Although various variables that affect cross-border knowledge flow have been posited such as geographical (Goodall and Roberts, 2003b) and psychic (Johanson and Vahlne, 1977) distances, there are few studies that examine in detail how these dimensions affect the MNC's ability to generate value from its highly dispersed cross-border knowledge. We postulated that local Chinese knowledge holders have huge physical and institutional gaps with global business specialists and they may also share some cultural features serving as human barriers for effective cross-border knowledge building.…”
Section: Contributions To Theorymentioning
confidence: 99%
“…A distinct spatial perspective is offered by a number of authors, whose interest is in regional science initiatives, demonstrating how knowledge practices develop in distinct locales or exhibit particular geographies. 57,58,60,61 Several authors discuss the nature of knowledge created, focusing either on the particular role of tacit knowledge [66][67][68] or on the nature of relational ties in knowledge networks. 69,70 These papers point to the range of information and ideas that can be integrated into collective problem-solving processes, echoing the points made in Chapter 1.…”
Section: The Main Themesmentioning
confidence: 99%
“…Thus, the Austrian approach considers that, not only do business actors lack knowledge, they are ignorant of the knowledge they lack (Forsgren, 2008b). Actors face a situation of 'sheer ignorance' (Kirzner, 1997) or radical uncertainty (Goodall and Roberts, 2003). If this can be accepted, we can argue that every sub-unit in the MNC suff ers from a certain degree of such ignorance, which also accounts for HQ, meaning that the HQ is unaware of the fact that it has a gap in its knowledge.…”
Section: Business Network Theory and The Role Of Headquartersmentioning
confidence: 99%
“…It has been argued that this causes a tension between the centre and the periphery in MNCs (Regnér, 1999). To the extent that coordination of activities between subsidiaries is one of the central tasks of an HQ, the diffi culties in fulfi lling the task are obvious, because the knowledge HQ has of what others know is a necessary component for coordinated action (Goodall and Roberts, 2003;Forsgren et al, 2005). The main reason for these difficulties is not lack of knowledge about the subsidiaries' operations as such, because this defi ciency can be dealt with by way of decentralization, integrative organizational forms, performance evaluation and so on.…”
Section: Business Network Theory and The Role Of Headquartersmentioning
confidence: 99%